SISTEM PELAPORAN KECELAKAAN LALULINTAS DENGAN PENDEKANAN GEOGRAPHICS INFORMATION SYSTEM - Edy Nasri; Mahmuman Mahmuman (Teknik Informatika Fakultas Ilmu Komputer, 2020)
Traffic accidents or road accidents are problems that often occur that are of particular concern, in order to minimize the number of accidents many find it difficult to report accidents and report accident-prone areas so that the community cannot know which areas have frequent accidents and which are accident-prone areas. Then the accident-prone areas were mapped with the Geographics Information System approach used in this research, namely in order to visually map the location of the accident location and the traffic accident-prone areas so that people can know directly the location point. In designing the system used in this study, namely by using the Waterfall Method, which has several stages including: Requirements analysis, system design, coding or writing program code, program testing, program implementation and maintenance. To model the system used is the Unified Modeling Language in this software engineering to describe the architecture and visualize a system to be built. So that this research can produce a software that can be accessed anywhere by the wider community to be able to report accidents and accident-prone areas where this case study was conducted in the Pandeglang Regency area.